2002
DOI: 10.1088/0268-1242/17/8/312
|View full text |Cite
|
Sign up to set email alerts
|

Interband transitions of quantum wells and device structures containing Ga(N, As) and (Ga, In)(N, As)

Abstract: The unusual N-induced band formation and band structure of Ga(N, As) and (Ga, In)(N, As) alloys are also reflected in the electronic structure of quantum wells (QWS) and device structures containing these non-amalgamation-type alloys. This review is divided into three parts. The first part deals with band structure aspects of bulk Ga(N, As) and motivates the possibility of a k•p-like parameterization of the band structure in terms of the level repulsion model between the conduction band edge of the host and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
34
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 91 publications
7
34
0
Order By: Relevance
“…The arrows indicate the effective band gap for each sample (obtained by least-squares fitting using Aspnes's lineshape model [7]). Examination of the data clearly reveals two trends as a function of increasing N-content: i) a rapid red-shift in the transition energies similar to the results found in prior studies on thick In y Ga 1-y As 1-x N x epilayers [3] and on a variety of dilute-N III-V MQWs [2]; (ii) a strong broadening in the line-shapes: this indicates that adding N increases the inhomogeneous broadening of the QW transitions [4].…”
supporting
confidence: 76%
See 2 more Smart Citations
“…The arrows indicate the effective band gap for each sample (obtained by least-squares fitting using Aspnes's lineshape model [7]). Examination of the data clearly reveals two trends as a function of increasing N-content: i) a rapid red-shift in the transition energies similar to the results found in prior studies on thick In y Ga 1-y As 1-x N x epilayers [3] and on a variety of dilute-N III-V MQWs [2]; (ii) a strong broadening in the line-shapes: this indicates that adding N increases the inhomogeneous broadening of the QW transitions [4].…”
supporting
confidence: 76%
“…In this new class of dilute-N III-N-V semiconductor alloys, modification in the band structure is achieved by N forming localised states which interact with the conduction band (CB) edge of the host semiconductor [3]. To investigate this complex band formation, modulation spectroscopy as a function of pressure, has proved to be a very useful tool [2][3][4]. Previously we reported the dramatic effects of increasing N-incorporation on the quantum well (QW) interband energies including negative bandgap-bowing, smaller total temperature variation, and strong decrease in the rate of pressure-shift (reduced linear shifts with larger sub-linear components) [4].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed studies on the nearest-neighbor environment of the substitutional N atoms in GaInNAs have shown that the fundamental band-gap energy in quaternary dilute nitride alloys is fairly sensitive to the local environmental conditions especially in the case of quantum well structures. 65,66 A more complicated modeling of the electronic structure based on pseudopotentials 67,68 requires a substantial computational effort. The numerical results are difficult to use.…”
Section: Band Anticrossingmentioning
confidence: 99%
“…The two approaches have been highly successful in describ-ing the band edge energies, and their variation upon annealing [17,18]. The BAC model has also been successfully applied to interpret photoreflectance (PR) measurements both of bulk and quantum well (QW) GaNAs samples at room temperature, identifying a higher energy feature (E + ) observed in bulk samples [16,19,20], and also providing a consistent interpretation of quantum well excited state transition energies across a wide range of samples, and as a function of hydrostatic pressure [21,22]. Despite the wide success of the BAC model, there has until recently been one significant set of experimental data which has remain unexplained, namely the observed composition dependence of the conduction band edge (CBE) effective mass in Ga(In)NAs alloys, in particular, at low temperatures.…”
Section: Introductionmentioning
confidence: 99%